Complexes of Usher proteins preassemble at the endoplasmic reticulum and are required for trafficking and ER homeostasis - Bernardo Blanco-Sánchez; Aurélie Clément; Javier Fierro; Philip Washbourne; Monte Westerfield (The Company of Biologists, 2014)
Usher syndrome (USH), the leading cause of hereditary combined hearing and vision loss, is characterized by sensorineural deafness and progressive retinal degeneration. Mutations in several different genes produce USH, but the proximal cause of sensory cell death remains mysterious. We adapted a proximity ligation assay to analyze associations among three of the USH proteins, Cdh23, Harmonin and Myo7aa, and the microtubule-based transporter Ift88 in zebrafish inner ear mechanosensory hair cells. We found that the proteins are in close enough proximity to form complexes and that these complexes preassemble at the endoplasmic reticulum (ER). Defects in any one of the three USH proteins disrupt formation and trafficking of the complex and result in diminished levels of the other proteins, generalized trafficking defects and ER stress that triggers apoptosis. ER stress, thus, contributes to sensory hair cell loss and provides a new target to explore for protective therapies for USH.